Career planning differences between male and female deaf students - Afdal, Afdal; Iswari, Mega; Alizamar, Alizamar; Ifdil, Ifdil; Syahputra, Yuda; Nurhastuti, Nurhastuti (Special Education, 2019)
This research aimed to study career planning differences between deaf male and female students. The study consisted of 96 deaf students of West Sumatra high school registered in the semester of January-June 2018, randomly selected by multiple random sampling. Furthermore, the Afdal Career Planning Inventory (ACPI), using the Likert Scale model was used to examine and analyze the study. The results showed no significant difference in the career planning of male and female deaf students. It also showed that the male deaf students are generally in the low category, while the female are in the medium.